Central bank digital currencies and banking: Literature review and new questions - James Chapman; Jonathan Chiu; Seyed Mohammadreza Davoodalhosseini; Janet Hua Jiang; Francisco Rivadeneyra; Yu Zhu (Bank of Canada, 2023)
We review the nascent but fast-growing literature on central bank digital currencies (CBDCs), focusing on their potential impacts on private banks. We evaluate these impacts in three areas of traditional banking: payments, lending, and liquidity and maturity transformation. For each area, we discuss the lessons learned and identify gaps in the research yet to be fully explored. We also take a broader look at CBDCs and highlight two promising directions for future research. One is to study CBDCs through the lens of industrial organization, exploring issues such as platform competition and business models. The second is the crypto space and its new developments such as stablecoins and decentralized finance.
Keywords: E50; E58; G00; L00; 330; Central bank research; Digital currencies and fintech; Financial institutions; Financial stability